Devotees engaged in darshan - Mumbai Archive Project Team (Jio Institute, 2024)
Devotees engage in darshan (the act of seeing and being seen by the deity) of the lingam from outside the garbhagriha, through the door that allows a clear view. The lingam is the primary focus of worship and rituals in the temple and is set on the floor of the garbhagriha, which is at a lower elevation than the temple.